The Esperpentos of "Martes de Carnaval" between Dehumanization and Exile - Mancinelli, Matteo (Madrygal. Revista de Estudios Gallegos, 2015)
This article tries to analyse the esperpentos of Martes de Carnaval focusing on the centrality that the motive of exile has in Valle-Inclán’s famous trilogy. A particular importance has to be recognized to concepts, such as interior exile and dehumanization, which allow the author to achieve his criticism against the corruption of the society in which he lives and to reason, at the same time, about the conidition of those who live the war horrific experience and survive.
Keywords: Ramón del Valle-Inclán; Martes de Carnaval; esperpentos; dehumanization; exile